Republic of Tajikistan : Financial System Stability Assessment Report. (IMF Staff Country Reports; Country Report ;, 2016)
This paper highlights Tajikistan's macroeconomic environment and gives an overview of the financial sector and its stability, and discusses its regulatory, supervisory, crisis prevention, and management framework. The economy of Tajikistan is entering a downturn, and the banking sector is showing substantial weakness. GDP growth has been on a declining trend. Inflation is also projected to rise further. The external position continues to deteriorate, putting pressure on the somoni and eroding already low external buffers. The financial sector of Tajikistan is dominated by banks, which account for 84 percent of total financial sector assets. Dollarization in the financial sector has been increasing and remains a challenge for foreign exchange risk and credit risk management.